The role of genotyping in measuring improved variety adoption and impact: Advances, challenges, and policy directions - Melesse, Mequanint B.; Maredia, Mywish K.; Wossen, Tesfamicheal; Odeny, Damaris; Spielman, David J.; Michelson, Hope; Waza, Showkat Ahmad; Kamunye, Kelvin; Alene, Arega; Dar, Manzoor H.; Afari-Sefa, Victor; Pingali, Prabhu (Elsevier, 2025)
Accurate measurement of agricultural technology adoption is critical for evaluating the effectiveness of investments in agricultural research and development. While household surveys have long served as the primary tool for tracking varietal adoption, growing evidence reveals systematic mismatches between self-reported and DNA verified varietal identity. These mismatches arise from distinct local and scientific varietal nomenclatures, complex seed systems, and high varietal release rates. This review examines the emerging role of genotyping, particularly DNA fingerprinting, as a complementary method for varietal identification and adoption measurement. Drawing on a growing body of studies across crops and geographies, we assess how DNA fingerprinting alters adoption estimates, reveals patterns of varietal misclassification, and enhances our understanding of seed system performance. We identify critical design considerations for implementing DNA fingerprinting at scale, including sampling strategies, reference library construction, and integration with standard household surveys. The review also highlights methodological innovations to reduce DNA fingerprinting costs and explores how fingerprinting can inform monitoring, evaluation, and scaling of agricultural innovations. Finally, we outline key research and policy priorities to mainstream DNA fingerprinting into national agricultural systems and to support more evidence-based, accountable, and equitable food policy.